2022
DOI: 10.1002/lio2.760
|View full text |Cite
|
Sign up to set email alerts
|

Operative technique in laryngeal paraganglioma: A case series and literature review

Abstract: Background: Laryngeal paragangliomas (LP) comprise a rare subset of head and neck neoplasms and are an important differential in the patient with a submucosal laryngeal mass. Methods:We discuss an operative technique using coblation assisted excision via laryngofissure in the cases of four confirmed LPs and discuss the current literature with respect to diagnosis and management of these patients.Results: Our case series of four patients demonstrate the laryngofissure approach for LP is safe, provides oncologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…In addition, it is reported that the endoscopic transoral approach has an extremely high recurrence rate of 80% versus the 17% recurrence of other surgical approaches [21]. Complete excision while preserving the surrounding structures is essential, primarily focusing on maintaining voice and swallowing functions [22].…”
Section: Treatment and Managementmentioning
confidence: 99%
“…In addition, it is reported that the endoscopic transoral approach has an extremely high recurrence rate of 80% versus the 17% recurrence of other surgical approaches [21]. Complete excision while preserving the surrounding structures is essential, primarily focusing on maintaining voice and swallowing functions [22].…”
Section: Treatment and Managementmentioning
confidence: 99%